STUDENTS’ MOTIVATION IN LEARNING ENGLISH BY GIVING WARM UP ACTIVITIES IN BEGINNING OF CLASS - Syahrul Syahrul (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
The objective of this research was to find out Students’ motivation in learning English by giving warm-up activities at the beginning of class, (An Experimental Study at the Second Grade of SMPN 2 Mangarabombang, Kabupaten Takalar). This research applied a pre-experimental design with Pre-Questionnaire, Treatment and Post-Questionnaire. The population of this research was the second-grade students of SMPN 2 Mangarabombang, Kabupaten Takalar which consisted of VIII A, VIII B, and VIII. To find out the students’ involvement motivation, the researchers used a questionnaire. The questionnaire aimed to find the effects of warm-up activities on students’ motivation in learning English. The questionnaire used an attitude scale, they were: Strongly Agree (SA), Agree (A), Undecided (UN), Disagree (D), or Strongly Disagree (SD). The students answered the question based on their perspective and their opinion. Warm-up activities affected the students’ perspective on learning English after being treated. The mean was improved by 8.24%, ranging from54.3 to 60.9. It indicates that students have a positive perspective on learning English after giving warm-up activities at the beginning of class. Warm-up activities affected the students’ extrinsic motivation in learning English after being treated. The mean is improved (5.78%) ranging from 55 to 59.56, which indicates that students’ extrinsic motivation is increased after giving warm-up activities at the beginning of class. It also shows that warm-up activities can create a good atmosphere and positive perspective for students and encourage students to be involved in classroom activities. Concern about that facts and based on the data analysis above and students’ journal analysis, the researcher would like to conclude that warm-up activities can affect students’ perspective and student's extrinsic motivation in learning English. So, we can make warm-up activities one of the options to face the class.